Self-investigation exercises: geometry learning strategies for prospective teacher students - Hamidah, Hamidah; Zaenuri, Zaenuri; Isnarto, Isnarto; Agoestanto, Arief (Journal of Education and Learning (EduLearn), 2025)
This study's purpose was to analyse the relationship between geometric thinking skills with self-regulated learning and with students' basic geometry skills. Furthermore, analyze student errors in solving geometry problems based on their self-regulated learning to determine the optimal geometry learning environment for geometry thinking skills. The study subjects were 46 second-semester students majoring in Mathematics Education for the academic year 2021/2022 of Universitas Bina Bangsa who were selected with purposive sampling techniques. This research uses quantitative and qualitative research methods. Data were obtained from geometric thinking ability tests, basic geometry skills tests, self-regulated learning questionnaires, and interview sheets. The results showed a relationship between the ability to think geometrically and the basic geometry skills of students in solving geometry problems in terms of student self-regulated learning. It was found that students' difficulties in solving geometry problems can be overcome by creating an independent geometry learning environment. The learning process design is an independent investigation exercise involving relevance, assurance, motivation, investigation, evaluation, and satisfaction.